ANALISIS YURIDIS PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA PADA PERNIKAHAN SIRI - Jannah, Raudhatul; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Marriage is a bond born inwardly between a man and a woman ashusband and wife with the aim of forming a happy and eternal family (household)based on the One Godhead. Marriage is carried out in front of the marriageregistrar employee so that a marriage certificate is obtained as proof of theoccurrence of marriage. Legal certainty is obtained if the case is decided basedon laws and regulations. Unlike serial marriages that cannot be proven to exist.Where the marriage is carried out secretly or secretly. So it cannot prove themarriage really happened or not. When there is violence in a serial marriage,judges cannot decide cases using the Domestic Violence Law just because theyconsider the elements of the household scope as husband and wife withoutchecking whether the marriage is valid or not according to the Marriage Law.The purpose of the study is to analyze the settlement of domestic violence crimesin series marriages in Indonesian positive law and ideally appropriate settlementsin deciding cases of domestic violence in series marriages.The research method used is normative juridical research using statutory,case and conceptual approaches.The results showed that if the judge’sconsideration in imposing a crime using article 44 paragraph (1) of the DomesticViolence Law is not appropriate when related to the Marriage Law, the elementsof the household scope as a married couple according to article 2 paragraph (1)of the Domestic Violence Law have not been fulfilled because the validity of themarriage contract they carried out has not been proven in court so that it is not inaccordance with the provisions of article 1 of the Marriage Law. The settlement inthe case is still considered inappropriate because if it is decided by the DomesticViolence Law, there is no distinction between a valid marriage and an invalidone. So that the case does not get legal certainty.Keywords: Domestic Violence, Siri Marriage, Legal certainty.